Comparative evaluation of teller and cardiff acuity tests in normals and unilateral amblyopes in under-two-year-olds - Sharma Pradeep; Bairagi Debasis; Sachdeva Murli; Kaur Kulwant; Khokhar Sudarshan; Saxena Rohit (Indian Journal of Ophthalmology, 2003)
Purpose: To compare and evaluate Teller Acuity Cards (TAC) and Cardiff Acuity Cards (CAC) to assess vision in children below the age of two. Methods: The study evaluated TAC and CAC to assess visual acuity in 90 normal children divided into three age groups, 0 - 6 months (group I), 6 - 12 months (group II) and 12 - 24 months (group III). 30 cases of unilateral amblyopiogenic conditions, 10 cases each of unilateral refractive error, unilateral esotropia, and unilateral cataract, were also examined. Trained optometrists carried out binocular testing followed by monocular testing, and recorded the test time in each case. Results: The mean visual acuity (in Snellen units) and standard deviation (in octaves) in the three age groups of normal children, I, II, III respectively were 6/44 ± 0.54, 6/21 ± 0.37 and 6/21 ± 0.41 (binocularly by TAC) and 6/46 ± 0.80, 6/21 ± 0.59 and 6/14.5 ± 0.84 (binocularly by CAC). Although the time taken for testing with CAC was less, its coefficient of variance was greater for all age groups as compared to TAC. Diminution of visual acuity could be assessed correctly by both the tests in cases of strabismus and cataract, but not in some cases of refractive error. Conclusion: CAC is a useful and child-friendly test. It can be used clinically but may miss some cases of visually significant refractive errors. TAC is a more dependable test to assess amblyopiogenic conditions despite the use of gratings.